2014
DOI: 10.1111/jonm.12246
|View full text |Cite
|
Sign up to set email alerts
|

First-line managers’ descriptions and reflections regarding their staff's access to empowering structures

Abstract: Managers could make use of performance and appraisal dialogues to keep up to date on staff's access to empowering structures. Recurrent discussions in the management group based on such current information could promote staff's access to power through empowering structures and make job definitions a strategic issue in the organisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…Regarding access to information, this was discussed in a more general form and not related specifically to their specific situation as IENs. The result is consistent with a Swedish study on managers’ views on staff (not specifically IENs but in general) access to operational workplace information (Skytt, Hagerman, Engström, & Strömberg, ). In contrast, research on IENs has found that they lacked information (Jose, ).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding access to information, this was discussed in a more general form and not related specifically to their specific situation as IENs. The result is consistent with a Swedish study on managers’ views on staff (not specifically IENs but in general) access to operational workplace information (Skytt, Hagerman, Engström, & Strömberg, ). In contrast, research on IENs has found that they lacked information (Jose, ).…”
Section: Discussionsupporting
confidence: 90%
“…FLMs are responsible for their unit's services, daily operations, finances, staff and clients (Hagerman, Engström, Häggström, Wadensten, & Skytt, ). Regarding their managerial position, managers have described having significant influence on their subordinates' work conditions and well‐being (Cummings et al, ; Holm & Severinsson, ) as well as on the quality of care (Skytt, Hagerman, Strömberg, & Engström, ) and patient safety (Wong, Cummings, & Ducharme, ). Regarding their own situation, one review reported that managers working with older persons and in hospitals have rated moderate stress levels in their work due to high job demands, heavy workloads, financial responsibilities and lack of resources (Labrague, McEnroe‐Petitte, Leocadio, Van Bogaert, & Cummings, ).…”
Section: Introductionmentioning
confidence: 99%
“…What was previously a role including both clinical work and supervision of nurses is today pure management (Ericsson & Augustinsson, 2015). The FLNMs' are a function just above the nurses, with FLNMs in turn reporting to management above themselves (Skytt et al, 2015). This can cause situations of conflict for the FLNM, for example, if production is the priority of management (Ericsson & Augustinsson, 2015).…”
Section: Introductionmentioning
confidence: 99%